The Role of Ficolins in Lung Injury - Meiyun Zhao; Xiaowu Tan; Xu Wu (Karger Publishers, 2024)
Background: Respiratory diseases seriously threaten human health worldwide, and lung injury is an important component of respiratory disease. Complement activation is an important function of the innate immune system. Complement activation helps the body defend against invasion by external microorganisms, whereas excessive complement activation can exacerbate tissue damage or lead to unwanted side effects. Ficolins are a class of immune-related proteins in the lectin pathway that play important roles in the body's immune defense. Although individual ficolins are not well understood, current information suggests that ficolins may play an important regulatory role in lung injury. Summary: Several studies have shown that ficolins are involved in the immune response in the lung, particularly in the response to infectious and inflammatory processes. Key Messages: This review summarizes the role of ficolins in lung injury. Ficolins may influence the development and repair of lung injury by recognizing and binding pathogenic microorganisms, modulating the inflammatory response, and promoting the clearance of immune cells. In addition, ficolins are associated with the development and progression of lung diseases (such as pneumonia and ARDS) and may have an important impact on the pathophysiological processes of inflammatory diseases.